PERAN PUSTAKAWAN DALAM MENINGKATKAN KINERJA DI PERPUSTAKAAN SMP NEGERI 8 PONTIANAK - Khalik, Idham; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe main role of librarians is to contribute to the mission  and purpose of library institutions including evaluation procedures and devaloping and implementing the mission and abjectives of the library. This stady aims to determine the role the librarians have perfomed in omproving  perfomance in the SMP Negri 8 Pontianak library. The data  collection method used is by interview, observation,and  documentation. Analysis  of the data  used is quqlitqtive  analysts. The role  that  librarians have taken in improving perfomance in the SMP Negri 8 Pontianak library includes educators,managers,administrators and supervisors. There are a number of things that became obstacles for librarians to improve library perfomance towards a better one.the contraints faced include inadequate sources of human resources(HR), librarians having difficulty withdrawing library finds by 5% from school operational assistance funds(BOS),lack of collections of library materials about novels and fiction, also inhibiting librarians from improving perfomance library. There needs to be attention from the school to help librarians improve the perfomance of the Pontianak National High School 8 library toword a better one. Keywords: the role of librarians,School library